An Emerging Clone, Klebsiellapneumoniae Carbapenemase 2–Producing K. pneumoniae Sequence Type 16, Associated With High Mortality Rates in a CC258-Endemic Setting. (12th November 2019) - Andrey, Diego O; Pereira Dantas, Priscila; Martins, Willames B S; Marques De Carvalho, Fabíola; Almeida, Luiz Gonzaga Paula; Sands, Kirsty; Portal, Edward; Sauser, Julien; Cayô, Rodrigo; Nicolas, Marisa F; Vasconcelos, Ana Tereza R; Medeiros, Eduardo A; et al.
Abstract: Background: Carbapenemase-producing Klebsiella pneumoniae has become a global priority, not least in low- and middle-income countries. Here, we report the emergence and clinical impact of a novel Klebsiella pneumoniae carbapenemase–producing K. pneumoniae (KPC-KP) sequence type (ST) 16 clone in a clonal complex (CC) 258–endemic setting. Methods: In a teaching Brazilian hospital, a retrospective cohort of adult KPC-KP bloodstream infection (BSI) cases (January 2014 to December 2016) was established to study the molecular epidemiology and its impact on outcome (30-day all-cause mortality). KPC-KP isolates underwent multilocus sequence typing. Survival analysis between ST/CC groups and risk factors for fatal outcome (logistic regression) were evaluated. Representative isolates underwent whole-genome sequencing and had their virulence tested in a Galleria larvae model. Results: One hundred sixty-five unique KPC-KP BSI cases were identified. CC258 was predominant (66%), followed by ST16 (12%). The overall 30-day mortality rate was 60%; in contrast, 95% of ST16 cases were fatal. Patients' severity scores were high and baseline clinical variables were not statistically different across STs. In multivariate analysis, ST16 (odds ratio [OR], 21.4; 95% confidence interval [CI], 2.3–202.8; P = .008) and septic shock (OR, 11.9; 95% CI, 4.2–34.1; P < .001) were independent risk factors for fatal outcome. The ST16 clone carried up to 14 resistance genes, including bla KPC-2 in an IncFIBpQIL plasmid, KL51 capsule, and yersiniabactin virulence determinants. The ST16 clone was highly pathogenic in the larvae model. Conclusions: Mortality rates were high in this KPC-KP BSI cohort, where CC258 is endemic. An emerging ST16 clone was associated with high mortality. Our results suggest that even in endemic settings, highly virulent clones can rapidly emerge demanding constant monitoring. Abstract : An emerging clone, Klebsiella pneumoniae carbapenemase 2–producing K. pneumoniae ST16, associated with high mortality rates in a CC258 endemic setting, was identified. This clone carried the KL51 capsule and displayed higher virulence in a Galleria larvae pathogenicity model than CC258 clones.